2016
DOI: 10.1120/jacmp.v17i5.6284
|View full text |Cite
|
Sign up to set email alerts
|

Surface dose variations in 6 and 10 MV flattened and flattening filter‐free (FFF) photon beams

Abstract: As the use of linear accelerators operating in flattening filter‐free (FFF) modes becomes more widespread, it is important to have an understanding of the surface doses delivered to patients with these beams. Flattening filter removal alters the beam quality and relative contributions of low‐energy X‐rays and contamination electrons in the beam. Having dosimetric data to describe the surface dose and buildup regions under a range of conditions for FFF beams is important if clinical decisions are to be made. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The surface dose was the subject of many research work [18][19][20][21][22]. Because the physical wedge, which is a medium atomic number absorber, can reduce the secondary electron scattering in the forward direction, it can reduce the surface dose.…”
Section: Discussionmentioning
confidence: 99%
“…The surface dose was the subject of many research work [18][19][20][21][22]. Because the physical wedge, which is a medium atomic number absorber, can reduce the secondary electron scattering in the forward direction, it can reduce the surface dose.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many studies are showing the advantages of FFF irradiation over FF irradiation [11][12][13][14][15][16] , and FFF is highly used in our clinic as in many centers. Especially with advancing technology and new RT devices, many studies are being done in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the surface dose difference was investigated using FFF and FF beams. 13,14 They reported that the FFF beam had slightly higher surface dose in the build-up region than the corresponding FF beam for a field size ≤10 × 10 cm 2 . They showed that the FFF beam contained more low-energy photons in the build-up region.…”
Section: Discussionmentioning
confidence: 99%